2018
DOI: 10.1089/fpd.2017.2341
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Contamination and Biofilm Formation by Salmonella enterica Serovar Enteritidis on Various Cutting Boards

Abstract: Cross-contamination is one of the main factors related to foodborne outbreaks. This study aimed to analyze the cross-contamination process of Salmonella enterica serovar Enteritidis from poultry to cucumbers, on various cutting board surfaces (plastic, wood, and glass) before and after washing and in the presence and absence of biofilm. Thus, 10 strains of Salmonella Enteritidis were used to test cross-contamination from poultry to the cutting boards and from thereon to cucumbers. Moreover, these strains were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 25 publications
(39 reference statements)
0
42
0
6
Order By: Relevance
“…Dantas et al [48] performed an experiment of microbial transfer of 10 biofilm forming S. enteriditis strains from chicken meat to cucumber via glass, plastic and wood cutting boards. The formation of biofilm was highest on wood (60%), followed by plastic (40%) and glass (10%).…”
Section: Microbial Adherence and Biofilm Formation On Wood Surfacementioning
confidence: 99%
“…Dantas et al [48] performed an experiment of microbial transfer of 10 biofilm forming S. enteriditis strains from chicken meat to cucumber via glass, plastic and wood cutting boards. The formation of biofilm was highest on wood (60%), followed by plastic (40%) and glass (10%).…”
Section: Microbial Adherence and Biofilm Formation On Wood Surfacementioning
confidence: 99%
“…Sci. 2019, 9, 4611 2 of 14 relevant role of cross-contamination in foodborne diseases [2][3][4][5][6][7]. Disinfection does not aim to sterilize surfaces but to reduce their microbial contamination to a safe, suitable level for their use [1].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been observed that biofilm formation occurs more on wooden surfaces (60%) than on plastic (40%) or glass (10%) boards [6], thus reinforcing the importance of strict hygiene practices for wooden cutting boards. A similar study conducted in the cities of India also showed that most foods sold in these cities' markets harboured pathogenic foodborne bacteria, such as Enterobacteriaceae, Staphylococcus spp.…”
Section: Introductionmentioning
confidence: 95%
“…For example, a study by Dantas et al [6] showed that the wooden cutting board surfaces were responsible for the transfer of microorganisms from poultry meat to cucumbers. The spread of Salmonella enterica serovar Enteritidis from poultry meat to cucumbers was assessed on different cutting board surfaces (wood, plastic, and glass) before and after washing of the surfaces.…”
Section: Introductionmentioning
confidence: 99%